The position of the Federal Supreme Court in United Arab Emirates on Guarantee Moral Damages in the event of non-Fatal Injuries - Al Yahyaee, Iman Khamis Al Yahyaee (Journal of Legal Sciences, 2025)
This research examines the position of the Federal Supreme Court in the United Arab Emirates on guaranteeing moral damage to spouses and relatives in the event of non-fatal injuries. We find that the Federal Supreme Court had an ancient approach stipulating the possibility of compensating spouses and relatives for the moral damage they suffer as a result of their relative’s injury, even if that injury did not lead to death, based on the principle of full compensation for damage.While the Supreme Court did not maintain the same position regarding the possibility of compensation for moral damages resulting from non-fatal injuries, as it ruled in most of its recent rulings to limit compensation to cases in which the injury leads to the death of the injured person. Spouses and relatives cannot be compensated for moral damages that are caused. As a result of their relative being injured, as long as he is still alive, and regardless of the degree of that injury.